Pass Laws and social reproduction: A reading of the 1956 women’s march and its aftermath - Mashele, Rixongile (University of the Witwatersrand, Johannesburg, 2024)
This thesis historically locates the experiences of ‘ordinary’ women in the context of restricted urban mobility, poor labour conditions, the disruption of family life and the pass system. Using archives and social reproduction as a conceptual lens, this research establishes that ‘ordinary’ black women knew what they were protesting for in 1956, that they understood the state’s efforts of consciously manipulating the costs of social reproduction, and its direct impact on their daily lives. They also understood that the experiences of men and women under apartheid were not the same. Importantly, these women utilised womanhood to fight against the apartheid state in their attempts of ensuring that African children receive access to resources and privileges equivalent to those of white children.
A research report submitted in fulfillment of the requirements for the Master of Commerce (Inequality Studies), In the Faculty of Faculty of Commerce, Law and Management, School of Economics and Finance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Pass Laws; Social reproduction; women’s political participation; SDG-5: Gender equality